DEVELOPMENT OF NATURAL SCIENCE LEARNING MEDIA ON ANIMAL METAMORPHOSIS MATERIALS BASED ON SCRATCH APPLICATIONS - Rahmawati, Ardiani Putri; Setyaningsih, Meyka Dina; Herawati, Umi Amiroh (Fakultas Ilmu Pendidikan, Universitas Persatuan Guru Republik Indonesia Semarang, 2024)
This study aims to design Scratch application-based learning media using animal metamorphosis material. This research method uses the Multimedia Development Life Cycle (MLDC) development model with six stages, namely concept, design, collecting, assembly, testing, and distribution. Two stages of testing were carried out, namely functionality testing to check the suitability of program functions and user acceptance testing to find out the user's response to the trial program that had been designed by distributing open questions via Google Forms and conducting interviews. The research participants were 18 students of the Elementary School Teacher Education study program at a university in Yogyakarta. Based on the research results, it was found that this learning media can be completed properly through the MDLC stages. In addition, the user response to the developed media is positive with a very good category. For the development of learning media, this media can be copyrighted and further research can be carried out with different materials along with research to find out the effectiveness of using the media that has been developed.